2003
DOI: 10.1080/0003942032000161072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ratio of ω6 : ω3 fatty acids and vitamin e levels in the diet on the reproductive performance of cockerels

Abstract: Three hundred and twenty 30-week old White Leghorn cockerels were housed in individual cages and distributed in a completely randomized factorial design of 5 x 3, with five oil sources (sunflower, soybean, canola, linseed and fish/soybean) and three levels of antioxidant (30, 200 and 400 mg of vitamin E/kg). The aim of this study was to evaluate the effect of the ratio of omega6: omega3 fatty acids by the inclusion of different oil sources and of dietary supplementation with vitamin E on the reproductive perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 9 publications
3
25
0
1
Order By: Relevance
“…Experiments on chickens have shown that feeding more PUFAs in the diet reduced the antioxidant status and quality of the semen (sperm concentration, semen volume). The importance of lipid peroxidation in this context was suggested by the ability of Vit.E, a chain breaking antioxidant, to reverse the negative impact of PUFA supplementation ( [Zanini et al, 2003] and [Cerolini et al, 2005]). …”
Section: Resultsmentioning
confidence: 99%
“…Experiments on chickens have shown that feeding more PUFAs in the diet reduced the antioxidant status and quality of the semen (sperm concentration, semen volume). The importance of lipid peroxidation in this context was suggested by the ability of Vit.E, a chain breaking antioxidant, to reverse the negative impact of PUFA supplementation ( [Zanini et al, 2003] and [Cerolini et al, 2005]). …”
Section: Resultsmentioning
confidence: 99%
“…In a study by Surai and colleagues [31], six-month-old male Rhode Island Red chickens were fed with a diet containing 0, 20, 200, or 1000 mg/kg α-tocopheryl acetate for eight weeks. During the final two weeks, they observed that the concentration of vitamin E in semen and sperms had doubled, and the susceptibility of the semen to lipid peroxidation was decreased, in particular in birds fed with 200 mg/kg of vitamin E. In another study [33], 30-week-old WL roosters were fed with a basal diet high in fish/soybean oil and with or without supplementation of vitamin E (30, 200, or 400 mg/kg). After 38 weeks, the roosters fed with fish/soybean oil showed the lowest total antioxidant status in the semen.…”
Section: Effects Of Dietary Vitamin E On Male Fertility Functions mentioning
confidence: 99%
“…With regard to male fertility, PUFAs are essential by virtue of their ability to confer upon the sperm plasma membrane the fluidity it needs to achieve fertilization. Experiments on chickens have shown that feeding more PUFAs in the diet reduced the antioxidant status and quality of the semen [81]. …”
Section: Results and Analysismentioning
confidence: 99%